To write the augmented matrix for the given system of equations, we need to rearrange the equations based on the standard form \(Ax + By + Cz = D\).
Let's first rewrite the equations so that they all have \(x\), \(y\), and \(z\) on the left and the constants on the right.
-
From the equation \( -4 - 2z = -y \):
- Rearranging gives us \(0x + y - 2z = -4\).
-
From the equation \( -3y + 2z = -2 \):
- This can be rearranged to \(0x - 3y + 2z = -2\).
-
From the equation \( z - 9y = -8x \):
- Rearranging gives us \(8x - 9y + z = 0\).
Now, we can represent the coefficients of \(x\), \(y\), and \(z\) along with the constants in the augmented matrix form.
The augmented matrix for this system of equations is:
\[ \begin{bmatrix} 0 & 1 & -2 & | & -4 \ 0 & -3 & 2 & | & -2 \ 8 & -9 & 1 & | & 0 \end{bmatrix} \]
Here, the vertical line separates the coefficients from the constants. Each row of the matrix corresponds to one of the equations in the system.